Schubert memorial in Stadtpark (in Vienna) - Perlberg (artist):::Creator::::::::::::; Rorich & Sohn (engraver):::Contributor::::::::::::; Kundmann, Karl (sculptor):::Contributor::::::::::::
Engraving of sculptor Karl Kundmann's memorial to Schubert in Vienna's Stadtpark, based on a drawing by Perlberg.